Acamprosate in the treatment of alcoholism: a budget impact analysis for the National Health Service in Italy - Colombo GL; Di Matteo S; Bruno G (Dove Medical Press, 2012)
Giorgio L Colombo,1,2 Sergio Di Matteo,2 Giacomo Bruno21Department of Drug Sciences, School of Pharmacy, University of Pavia, Pavia, Italy; 2S.A.V.E. – Studi Analisi Valutazioni Economiche, Milan, ItalyObjective: Alcohol dependence is a common condition associated with high direct and indirect health care costs. The purpose of this analysis was to estimate the economic consequences of acamprosate used as adjuvant therapy in the treatment of alcoholism, defining a budget impact analysis (BIA) from the point of view of the Italian National Health Service (NHS).Methods: We developed a model of disease evolution related to alcoholism using data from the PRAMA study. The hypothetical population included in the decision model was obtained from data from the Ministry of Health. We compared the following treatment strategies: no treatment, standard care (psychotherapy), sodium oxybate (sodium salt-4-hydroxybutyric acid), and acamprosate. The time horizon of the model was 10 years. The costs were evaluated from the NHS perspective.Results: We simulated the path for 69,348 patients treated at the outpatient clinics of the Addiction Services (SerT), and 38,911 patients discharged from hospital. Patients in the acamprosate group had lower alcohol-related events, with a reduction of the total cost. The BIA shows that the increase in the use of acamprosate was associated with a progressive decrease of total costs, calculated as the sum of the diagnosis-related groups (DRG), rehabilitation, and drug costs. The increasing use of acamprosate instead of standard care and sodium oxybate would generate cost savings up to over €6 million over 10 years of simulation.Conclusion: The estimates in the model are based on hypothetical situations; the assumptions of the model as well as their specific impact on treatment effect estimations and clinical implications should be validated in real life. Public health care authorities would benefit from mathematical models designed to estimate the future burden of alcohol dependence together with the impact of treatment and the potential to reduce the incidence and progression of this condition, and the costs of its complications.Keywords: alcohol dependence, acamprosate, budget impact analysis, economic evaluation